Early Waste Education for Elementary School Students with Animation Videos: Edukasi Dini Sampah bagi Siswa Sekolah Dasar dengan Video Animasi - Diana, Elviza; Tonadi, Een; Sefrus, Tri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The problem is a serious problem related to waste handling between 2013 and 2023. This problem includes an increase in the amount of waste that is not commensurate with the capacity of waste disposal sites which are already overloaded. The two main factors that cause this problem are a lack of public awareness of the importance of waste management and a lack of knowledge about how to use waste wisely. To overcome this problem, a community service program has been designed with a focus on early education about waste and its use, especially aimed at school students. basic at SDIT Rabbani. This activity aims, among other things, to provide students with a basic understanding of waste, how waste can damage the environment and threaten the lives of living creatures. Through this understanding, it is hoped that students will be more aware of the importance of protecting the environment from an early age. Students will be actively involved in waste management at school, given certain tasks and responsibilities in maintaining the cleanliness of the school environment. This will help them internalize the values ​​of preserving and protecting the environment. Apart from providing education, this program also facilitates adequate waste disposal sites and teaches students the correct way to sort waste. This is an important step to improve overall waste management. The Implementation Method involves several stages, including preliminary studies, program design, program implementation and evaluation